Rape Work : Victims, Gender, and Emotions in Organization and Community Context. - Martin, Patricia Yancey (Perspectives on gender., 2013)
Despite the proliferation of rape crisis centers and other improvements in the treatment of rape victims over the past 20 years, many victims still find themselves the victims of what has been called a ""second rape"" by doctors, lawyers, judges, police, and administrators that process them. This book takes a critical look at the organizations and officials that process rape victims to see how the structure of their respective organizations often prevent them from providing responsive care.